Fuzzy-Logic Approach to Estimate the Passengers’ Preference when Choosing a Bus Line within the Public Transport System - Vitalii Naumov; Baurzhan Zhamanbayev; Dinara Agabekova; Zhumazhan Zhanbirov; Igor Taran (Communications - Scientific letters of the University of Zilina, 2021)
For the developed system of public transport, the passengers, as the customers, have a variety of alternatives when choosing the transport mode or even the route for the given mode of public transport. The estimation of the passengers’ preference is the key task for transportation planners for solving the wide range of optimization problems in the field of public transport. A methodology for estimation of the passengers’ preference when choosing the bus line within a public transport system is developed in this paper. The proposed approach is based on the fuzzy-logic mathematical apparatus and uses the surveys’ data to calculate the membership functions defining the passengers’ preference. The case study of the passengers’ survey, held in Talas (Kazakhstan), is used to illustrate the developed methodology.